Adaptive modulation with constrained variable power for space-time coded MIMO systems - Yu, Xiangbin; Liu, Xiaoshuai; Zhu, Qiuming; Xu, Dazhuan (International journal of communication systems, 2014)
SUMMARYPractically, the maximum transmission power of transmission systems is limited. This power constraint causes the variable power control derived from no maximum power limitation suffering from performance degradation. In this paper, a constrained variable‐power adaptive M‐ary quadrature amplitude modulation scheme for MIMO systems with space–time coding is developed. Convex optimization is used to derive the switching thresholds of the instantaneous signal‐to‐noise ratio for power control (PC) and adaptive modulation under the constraints of maximum power, average power, and target BER. In the derivation of the relation between modulation and power, the exact BER expression of binary phase shift keying modulation and a tight bound for higher order quadrature amplitude modulation are used to make the PC scheme fulfill the target BER even at low signal‐to‐noise ratio where the previous PC schemes fail to meet the target BER. Numerical results show that the derived control scheme under the power constraints can obtain the spectrum efficiency and BER performance close to the previous control scheme without power limitation. Moreover, it can satisfy the requirements of power limitation and target BER and can effectively avoid the excessive power consumption of previous PC scheme in poor channel condition. Copyright © 2012 John Wiley & Sons, Ltd. A constrained variable‐power adaptive modulation (AM) scheme for space‐time coded MIMO systems is developed. Convex optimization is used to derive the switching thresholds of the signal‐to‐noise ratio for power control (PC) and AM under the constraints of maximum power, average power, and target BER. Numerical results show that the derived PC can obtain the spectrum efficiency and BER performance close to the previous control scheme without power limitation. Moreover, it satisfies the requirements of power limitation and target BER.